2019
DOI: 10.1056/nejmoa1811714
|View full text |Cite|
|
Sign up to set email alerts
|

Overall Survival with Fulvestrant plus Anastrozole in Metastatic Breast Cancer

Abstract: BACKGROUND We previously reported prolonged progression-free survival and marginally prolonged overall survival among postmenopausal patients with hormone receptor–positive metastatic breast cancer who had been randomly assigned to receive the aromatase inhibitor anastrozole plus the selective estrogen-receptor down-regulator fulvestrant, as compared with anastrozole alone, as first-line therapy. We now report final survival outcomes. METHODS We randomly assigned patients to receive either anastrozole or ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 16 publications
2
65
0
6
Order By: Relevance
“…43 A subgroup analysis in this trial suggested that patients without prior adjuvant tamoxifen experienced the greatest OS benefit with combination therapy compared with monotherapy (median, 52.2 vs 40.3 months, respectively; HR, 0.73; 95% CI, 0.58-0.92). 44 The reasons for the divergent outcomes in these trials are not very clear. The 3 trials discussed previously had slightly different patient populations.…”
Section: Single Agent Fulvestrantmentioning
confidence: 99%
“…43 A subgroup analysis in this trial suggested that patients without prior adjuvant tamoxifen experienced the greatest OS benefit with combination therapy compared with monotherapy (median, 52.2 vs 40.3 months, respectively; HR, 0.73; 95% CI, 0.58-0.92). 44 The reasons for the divergent outcomes in these trials are not very clear. The 3 trials discussed previously had slightly different patient populations.…”
Section: Single Agent Fulvestrantmentioning
confidence: 99%
“…The updated results of SWOG 0266 showed improvement in overall survival by combination therapy with anastrozole and AI, especially among patients without receiving previous endocrine therapy [20]. We did not include this finding, because our systematic review is restricted to the study published until 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Selective estrogen receptor degrader (SERD) such as fulvestrant, are pure anti-estrogens that blocks estrogen receptor and degrades the receptor without any agonist effect [120]. Fulvestrant was first used in 2002 as a 'SERD hormone therapy' against HR + HER2 − advanced and metastatic breast cancer in post-menopausal women that were resistant to other hormone therapy [121]. It is used in combination with CDK4/6 inhibitors like palbociclib (PALOMA-3) and ribociclib (MONALEESA-3) and anti-PI3K/AKT/mTOR pathway drugs such as pictilisib (FERGI) and buparlisib (BELLE-2 and BELLE-3) [122].…”
Section: Hormone Therapy or Endocrine Therapymentioning
confidence: 99%